Attributes of Iranian new nurse preceptors: A phenomenological study. (January 2018) - Borimnejad, Leili; Valizadeh, Sousan; Rahmani, Azad; Whitehead, Bill; Shahbazi, Shahla
Abstract: Preceptors should possess attributes which help them in successfully performing the demanding and challenging role in the preceptorship. This research utilises a qualitative hermeneutic phenomenological approach to explore the attributes of new nurse preceptors. Six preceptors of a teaching hospital in Northwest of Iran who were selected by means of purposive sampling. Data were collected during eight months from July 2014 to March 2015 through in-depth semi-structured personal interviews. Interviews were recorded and transcribed and then were analyzed with the interpretive approach using the Diekelmann's seven-stage method in the MAXQDA10 software environment. Findings included two main themes "feeling proud and honored" and "professionalism" with subthemes including empathy, being nonjudgmental, patience, and spirit of self-sacrifice. The spirit of self-sacrifice was a unique attribute revealed in this research. Preceptors possessed several important attributes which are usually stressed in the literature as selection criteria for preceptors. These attributes could be further drawn upon when selecting new preceptors. Preceptors are role models. Existence of the spirit of self-sacrifice among preceptors could contribute to transferring of such spirit to new nurses and future preceptors as well as to preceptors' patience with challenges of their role. Effective preceptorship needs preceptors who possess specific professional and personal attributes. These attributes could be drawn upon more objectively in the process of selection, preparation and evaluation of preceptors by clinical and educational nursing managers. Highlights: Empathy of preceptors could indicate applicability of Travelbee's human-to-human relationship model to preceptorship. Existence of the spirit of self-sacrifice among preceptors could contribute to transferring of such spirit to new nurses. To decrease the risk of 'preceptor burnout', preceptors should be supported during the proctorship program. Preceptors demonstrate the spirit of self-sacrifice to compensate for extra workload of Precepting.